2015
DOI: 10.1080/00918369.2014.1003009
|View full text |Cite
|
Sign up to set email alerts
|

Are LGBT Populations at a Higher Risk for Suicidal Behaviors in Australia? Research Findings and Implications

Abstract: The aim of this article is to review the Australian literature about suicidality in minority sexual identity and/or behavior groups in order to determine the evidence base for their reported higher vulnerability to suicidal behaviors than heterosexual and non-transgendered individuals in the Australian context, as well as to identify the factors that are predictive of suicidal behaviors in these groups in Australia. A literature search for all available years (until the end of 2012) was conducted using the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Non-systematic and non-representative data collection. There is a need for the systematic inclusion of measures on sexual minority status in population-based surveys and other forms of large-scale data collections in order to generate representative datasets with information on sexual orientation (Blais et al, 2015;Blondeel et al, 2018;Brennan et al, 2017;Goldbach et al, 2014;Haas et al, 2011;Lannert, 2015;Russell & Fish, 2016;Semlyen et al, 2016;Skerrett et al, 2015). Representative datasets of sexual minority populations could further facilitate the generalizability of findings, as convenience sampling may often lead to the underrepresentation of certain subgroups, like those concealing their sexual identity (Meyer & Wilson, 2009).…”
Section: Outness -mentioning
confidence: 99%
See 1 more Smart Citation
“…Non-systematic and non-representative data collection. There is a need for the systematic inclusion of measures on sexual minority status in population-based surveys and other forms of large-scale data collections in order to generate representative datasets with information on sexual orientation (Blais et al, 2015;Blondeel et al, 2018;Brennan et al, 2017;Goldbach et al, 2014;Haas et al, 2011;Lannert, 2015;Russell & Fish, 2016;Semlyen et al, 2016;Skerrett et al, 2015). Representative datasets of sexual minority populations could further facilitate the generalizability of findings, as convenience sampling may often lead to the underrepresentation of certain subgroups, like those concealing their sexual identity (Meyer & Wilson, 2009).…”
Section: Outness -mentioning
confidence: 99%
“…Representative datasets of sexual minority populations could further facilitate the generalizability of findings, as convenience sampling may often lead to the underrepresentation of certain subgroups, like those concealing their sexual identity (Meyer & Wilson, 2009). Such datasets would enable the assessment of mental health disparities over time and systematically collected data would facilitate the possibility to pool data to create large enough datasets for the examination of the intersectionality of sexual minority status with various other stigmatized identities (Blais et al, 2015;Blondeel et al, 2018;Bränström et al, 2019;Brennan et al, 2017;Goldbach et al, 2014;Haas et al, 2011;Lannert, 2015;Russell & Fish, 2016;Semlyen et al, 2016;Skerrett et al, 2015).…”
Section: Outness -mentioning
confidence: 99%
“…A review of the evidence base for a heightened vulnerability to suicidal behaviors among LGBTI populations in Australia by Skerrett et al . (; ) found that sexual minorities are indeed at a higher risk for nonfatal suicidality.…”
Section: Introductionmentioning
confidence: 98%
“…Skerrett et al . (; ) reported that there were no existing studies on the relationship between those that have died by suicide and sexuality in Australia at the time of writing.…”
Section: Introductionmentioning
confidence: 99%
“…Lesbians, gays, and bisexual people (LGB) present higher levels of self-harm, suicidal ideation, and attempted suicide than heterosexuals [ 1 , 2 , 3 , 4 , 5 ]. French studies have yielded similar results [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%